Overgrowth the transformation of the landscape narrative of the Manila Film Center through the lens of Lino Brocka - Valera, Emilia Gabrielle S.
Brutalism in the Philippines has always been associated with the reign of Marcos. Despite this era of cultural and technological advancements, the negative impact of his administration still continues to loom over the history of the Philippines. Because of this, structures that are linked to this dark era have been abandoned and neglected such as the Manila Film Center in the Cultural Complex of the Philippines. This study aims to transform the narrative of the landscape of this abandonment into something that will promote the culture of the Filipinos in the film industry and encourage future filmmakers through giving them a permanent and tangible address to house and showcase their work. This transformation would be done using urban greening and greening buildings strategies while applying nature-based solutions, place making theories, biophilia theories, and attention-restoration theory.